'Like a "fish in water"': swim club membership and the construction of the upper-middle-class family habitus. Issue 3 (3rd May 2016) - DeLuca, Jaime R.
Abstract : Cultural theorist Pierre Bourdieu's concept of habitus has been widely operationalised in relation to sport, yet there has been little scholarship considering the notion of family habitus . Through ethnographic methods, this research offers an empirically based analysis delineating the way in which the Valley View Swim and Tennis Club is a constitutive element of members' upper - middle-class family habitus . Specifically, I argue that swim club membership is anchored in a distinct family tradition and offers members an important cultural field facilitating their experience of family time. However, members' routine trips to the pool are naturalised, taken-for-granted elements of their summer lifestyles emblematic of their class privilege, and thus club membership operates as a valuable, yet subtle technique to reproduce their upper-middle-class family habitus.